Land grab : green neoliberalism, gender, and Garifuna resistance in Honduras - Brondo, Keri Vacanti (University of Arizona Press, 2013)
This book is an ethnographic account of the relationship between identity politics, neoliberal development policy, and rights to resource management in Garifuna communities on the north coast of Honduras, before and after the 2009 coup d’état.